Ekstraksi Crude Tanin dari Daun Rambutan Dengan Metode Sonikasi dan Maserasi - Istiqo Mustaqim; R Vanji Habibul M (Publikasi Indonesia, 2022)
At this time rambutan fruit is very popular among the community. Do we know that when we usually pick rambutan fruit, we will also pick the leaves of the rambutan, with the situation in society like this we usually throw the leaves in the trash or we burn them. Can it be known that in rambutan leaves which become organic waste there is a 6% tannin content. The purpose of this study was to find the best contact time in sonication and to find the best tannin weight of rambutan leaves by sonication and maceration methods. From the test results, it can be seen that the more materials and solvents are sonicated, the greater the tannin obtained. The highest tannin content was seen in the variable 30/150 at a sonication time of 60 minutes, namely 7.6502%, it can be concluded that the optimal time of the sonication process to obtain the highest tannin content is at a time of 60 minutes and the weight per volume ratio at 30/150 gr/ml. The highest tannin content is about 7.6502%. With this it can be concluded that tannin can still experience an increase or decrease in this sonication extraction seeing the results have not reached the best level, namely with stationary results with a time of 75 minutes 30/150 gr / ml still decreased and other time variables still increased. It can be said that from this it can still be developed again extraction with higher variables of time and weight of extracted rambutan leaves.